Electrical properties of fast cooled inse single crystals - Zaslonkin, A.V.; Kovalyuk, Z.D.; Mintyanskii, I.V.; Savitskii, P.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Influence of fast cooling on electrical properties of n-InSe single crystals is
investigated for an ingot grown by the Bridgman method. Electrical characteristics and
their anisotropy are investigated in the temperature range 80 to 410 K. It is found that
fast cooling, as soon as crystallization is completed, of the ingot leads to an increase of
the free electron concentration, conductivity along layers, and conductivity anisotropy, as
well as to a decrease of the Hall mobility of carriers along layers. The theoretical analysis
of the mobility of carriers has shown that space-charge regions underlie the effective
mechanism of their scattering.